SISTEM INFORMASI PRESENSI GURU BERBASIS QR-CODE PADA SMAN 1 WAYLIMA - Fitriani, Salwa Nur; Puspitasari, Tuti (YHMM PUBLISHING, 2024)
Efficient and accurate teacher attendance management is an important aspect in education management. For this reason, we need a system that is able to record attendance quickly and reduce the risk of data errors. This research developed a QR CODE-based teacher attendance information system using the Waterfall method and the PHP programming language. The Waterfall method was chosen because of its systematic sequential approach in software development, which includes the stages of requirements analysis, system design, implementation, testing and maintenance. This system utilizes QR CODE technology for the attendance process, where each teacher has a unique code which is scanned when present. The research results show that this system is able to increase the efficiency and accuracy of attendance recording compared to conventional methods. Apart from that, this system also makes it easy to manage attendance data and generate reports that can be accessed in real-time by related partie.